A Systematic Review Of Arabic Phonetic: Hijaiyyah’s Pronunciation Among New Learners - Mohamed, Yuslina; Razak, Zainurrijal Abd; Ismail, Tuan Haji Sulaiman; Alribdi, Nada Ibrahim; Hoque, Mesbahul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Makhraj or pronunciation is an essential element of Arabic phonetic rules in the Quranic reading. Studies on the articulateness of Arabic alphabet pronunciation of phonetic aspects due to the influence of native languages have been debated for decades. The Makhraj of Hijaiyyah is related to learning and reading the Quran, as the Quran itself is revealed in Arabic. Therefore, the consonant of Hijaiyyah's pronunciation must be mastered at the beginning of the Quranic study to produce a clear sound and precise meaning. This study aims to acquire a pattern of Hijaiyyah consonant designation in terms of the characteristics of the Malay tongue's articulation fluency, consonants, and phonetic nature for the basis of Quranic learning and teaching. The content analysis method developed a theme related to the pronunciation fluency of letters in three levels. The classification of letters is emphasized to guide teachers and other researchers in teaching the Arabic language and al-Quran education.